A new hybrid matheuristic optimization algorithm for solving design and network engineering problems. Issue 1 (2nd January 2018) - Chagwiza, G.; Jones, B. C.; Hove-Musekwa, S. D.; Mtisi, S.
Abstract: A hybrid matheuristic algorithm is formulated by combining Grotschel–Holland and Max–Min Ant System algorithms to solve design and network engineering problems. In the majority of our examples, the hybrid algorithm seems promising. The matheuristic has the ability to increase exploration and it maximizes exploitation of various solutions and the certainty of exact methods to find a solution. Further, a recommended study direction is to improve the algorithm to solve higher-order polynomial type problems efficiently.